Implementasi Konsep Merdeka Belajar Melalui Pembelajaran yang Berpusat pada Murid dengan Menggunakan Model Pembelajaran Berbasis Masalah Materi Statistik Kelas XII SMA Negeri Matakali Tahun Ajaran 2021/2022 - Hastomo Machfud (AIJER: Algazali International Journal Of Educational Research, 2022)
Abstract: Implementation of the Concept of Freedom to Learn through Student-Centered Learning Using a Problem-Based Learning Model for Class XII Statistical Materials at Matakali State High School in the Academic Year 2021/2022. This study aims to determine the effectiveness of mathematics learning through a problem-based learning model on the implementation of an independent learning curriculum in class XII science students of SMA Negeri Matakali for the 2021/2022 academic year consisting of 22 students using class action research. The data collection instruments used are tests, observations, and questionnaires. The data analysis techniques used are descriptive analysis and inferential analysis using the t-test one sample test. The results of this study show that hypothesis testing obtained a sig value (2-tailed) = 0.000 < α = 0.05.Based on the results of the study, it can be concluded that there is an increase in the effectiveness of mathematics learning through the Problem Based Learning (PBL) model on the concept of independent learning in Class XII science at Matakali State High School.